Serial killers : philosophy for everyone : being and killing - 4 0 16; Waller, S.; 5 (Chichester, West Sussex, UK : Wiley-Blackwell, 2010)
Examines the interest in serial killers, discussing existential, ethical, and political questions while examining real and fictional murderers.
Introduction: meditations on murder, or what is so philosophical about serial killers? / S. Waller and William E. Deal -- Man is the most dangerous animal of all : a philosophical gaze into the writings of the Zodiac Killer / Andrew M. Winters -- A philosophy of serial killing : Sade, Nietzsche, and Brady at the gates of Janus / David Schmid -- The situation of the jury : attribution bias in the trials of accused serial killers / Mark Alfano -- Serial killers as practical moral skeptics : a history with interviews / Amanda Howard -- Are psychopathic serial killers evil? Are they blameworthy for what they do? / Manuel Vargas -- Sympathy for the devil : can a serial killer ever be good? / Matthew Brophy -- The allure of the serial killer / Eric Dietrich and Tara Fox Hall -- Dexter's dark world : the serial killer as superhero / Susan Amper -- Killing with kindness : nature, nurture, and the female serial killer / Elizabeth Schecter and Harold Schecter -- It puts the lotion in the basket : the language of psychopathy / Chris Keegan -- Are serial killers cold-blooded killers? / Andrew Terjesen -- The serial killer was (cognitively) framed / William E. Deal -- Wolves and widows : naming, metaphor, and the language of serial murder / Wendy M. Zirngibl -- An arresting conversation : police philosophize about the armed and dangerous / S. Waller (with Diane Amarillas and Karen Kos) -- Psychopathy and will to power : Ted Bundy and Dennis Rader / Richard M. Gray -- The thread of death, or the compulsion to kill / J.S. Piven -- Afterword: a solemn afterword : a message from the victim's network / Mary Miller.
Includes bibliographical references.
Adult;Adult.
Keywords: 2 -- 0; 6; Psychology.;Psychology. -- Serial murderers;Psychology, Pathological.;Serial killers;Abnormal psychology; 20; 2